Cannabinoids and Innate Immunity: Taking a Toll on Neuroinflammation - Eric J. Downer (The Scientific World Journal)
The biologically active components of cannabis have therapeutic potential in neuroinflammatory disorders due to their anti-inflammatory propensity. Cannabinoids influence immune function in both the peripheral and the central nervous system (CNS), and the components of the cannabinoid system, the cannabinoid receptors and their endogenous ligands (endocannabinoids), have been detected on immune cells as well as in brain glia. Neuroinflammation is the complex innate immune response of neural tissue to control infection and eliminate pathogens, and Toll-like receptors (TLRs), a major family of pattern recognition receptors (PRRs) that mediate innate immunity, have emerged as players in the neuroinflammatory processes underpinning various CNS diseases. This review will highlight evidence that cannabinoids interact with the immune system by impacting TLR-mediated signaling events, which may provide cues for devising novel therapeutic approaches for cannabinoid ligands.